Text on front: 'Commune de Lyon ...'. Text on back. Dedication by Joubert on back: 'Défence de Paris 1870-1871. Souvenir d'un ami'
Text on front: 'Commune de Lyon ...'. Text on back. Dedication by Joubert on back: 'Défence de Paris 1870-1871. Souvenir d'un ami'.